2013
DOI: 10.1155/2013/516052
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Illumination Normalization Method Based on Mean Estimation for Face Recognition

Abstract: An illumination normalization method for face recognition has been developed since it was difficult to control lighting conditions efficiently in the practical applications. Considering that the irradiation light is of little variation in a certain area, a mean estimation method is used to simulate the illumination component of a face image. Illumination component is removed by subtracting the mean estimation from the original image. In order to highlight face texture features and suppress the impact of adjace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…From the UFE methods, multi‐OGPF [86], wGAP [93] and NDF [83] provided 100% accuracy. From the UP group, mean‐LDA [54], DD‐DTCWT [78] and fuzz + LFDCT [60] had the same results. In the same way, the 9‐basis [38] relighting approach had a full recognition result.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the UFE methods, multi‐OGPF [86], wGAP [93] and NDF [83] provided 100% accuracy. From the UP group, mean‐LDA [54], DD‐DTCWT [78] and fuzz + LFDCT [60] had the same results. In the same way, the 9‐basis [38] relighting approach had a full recognition result.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [53] decomposed the image into two new images, and then applied a minimum‐and‐maximum filter to the high‐frequency part and a shadow removal to the low‐frequency part. Luo et al [54] suggested the use of a mean estimation method to simulate the illumination component of the image. Then, a post‐processing step is performed to reduce noise and highlight facial texture features.…”
Section: Unlightingmentioning
confidence: 99%